2018
DOI: 10.1155/2018/4047386
|View full text |Cite
|
Sign up to set email alerts
|

Association between Traffic Related Air Pollution and the Development of Asthma Phenotypes in Children: A Systematic Review

Abstract: Introduction Traffic related air pollution (TRAP) has long been associated with the onset of childhood asthma. The relationship between TRAP exposure and the development of childhood asthma phenotypes is less understood. To better understand this relationship, we performed a systematic review of the literature studying childhood TRAP exposure and the development of childhood asthma and wheezing phenotypes (transient, persistent, and late-onset asthma/wheezing phenotypes). Methods A literature search was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The results from our statistical models indicate that the odds of having asthma/asthma like symptoms for children with reported high neighborhood tra c was 78% higher than the odds for children without There has been mounting evidence of a causal effect of TRAP exposures on asthma exacerbations. 56 Our ndings are consistent with the results of a prospective study in Sweden (n ~ 4000) which found positive associations between early life air pollution exposures (PM 10 and NO 2 ) and asthma exacerbations. 57 The Cincinnati birth cohort study (n ~ 700) also detected associations between particulate air pollution exposure and wheezing during infancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results from our statistical models indicate that the odds of having asthma/asthma like symptoms for children with reported high neighborhood tra c was 78% higher than the odds for children without There has been mounting evidence of a causal effect of TRAP exposures on asthma exacerbations. 56 Our ndings are consistent with the results of a prospective study in Sweden (n ~ 4000) which found positive associations between early life air pollution exposures (PM 10 and NO 2 ) and asthma exacerbations. 57 The Cincinnati birth cohort study (n ~ 700) also detected associations between particulate air pollution exposure and wheezing during infancy.…”
Section: Discussionsupporting
confidence: 91%
“…A 2017 meta-analysis of 41 epidemiologic studies provided evidence for the hypothesis that childhood exposure to TRAP contributes to the development of asthma, and called for further studies. 61 A recent review, based on seven studies, concluded that TRAP exposures may be associated with transient and persistent asthma/wheezing phenotypes in children, 56 and also stressed the need for more studies on these phenotypes. As children's early life and current exposures to TRAP appears to play a key role in asthma development, 18 carefully designed studies are needed to understand this relationship and identify critical windows for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…There has been mounting evidence of a causal effect of TRAP exposures on asthma exacerbations [ 56 ]. Our findings are consistent with the results of a prospective study in Sweden ( n ~4000) which found positive associations between early life air pollution exposures (PM 10 and NO 2 ) and asthma exacerbations [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 meta-analysis of 41 epidemiologic studies provided evidence for the hypothesis that childhood exposure to TRAP contributes to the development of asthma, and called for further studies [ 61 ]. A recent review, based on seven studies, concluded that TRAP exposures may be associated with transient and persistent asthma/wheezing phenotypes in children [ 56 ], and also stressed the need for more studies on these phenotypes. As children’s early life and current exposures to TRAP appears to play a key role in asthma development [ 18 ], carefully designed studies are needed to understand this relationship and identify critical windows for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a major compound of wall for Gem-negative bacteria, and also acts as a significant immunostimulatory component of air pollution. Both epidemiological studies and animal experiments have demonstrated that exposure to LPS can sensitize or exacerbate COPD and asthma by promoting Th2 responses [8]. We have identified that a Th2 cytokines-dominant airway microenvironment similar to asthma was triggered during the later stage of RSV infection [9].…”
Section: Introductionmentioning
confidence: 95%